Data brokers co-opetition - Yiquan Gu; Leonardo Madio; Carlo Reggiani (Center for Economic Studies and ifo Institute (CESifo), 2019)
Data brokers collect, manage, and sell customer data. We propose a simple model, in which data brokers sell data to downstream firms. We characterise the optimal strategy of data brokers and highlight the role played by the data structure for co-opetition. If data are “sub-additive”, with the combined value lower than the sum of the values of the two datasets, data brokers share data and sell them jointly. When data are “additive” or “supra- additive”, with the combined value equal to or greater than the sum of the two datasets, data brokers compete. Results are robust to several extensions.
Keywords: D43; L13; L86; M31; 330; data brokers; personal information; privacy; co-opetition